A Study of Sustainable Palm Oil Model as Energy Source Considering the Economic, Social, Enviromental and Security Balance Variables - Nasution, Aswin; Fajri, Fajri; Karim, Abubakar; Romano, Romano (International Journal of Energy Economics and Policy, 2020)
As energy source, palm oil has become a serious concern for various palm oil stakeholders because it is related to the vegetable oil needs for 7.7 billion people in the world. Nagan Raya District is a central of palm oil in the western region of Aceh and inseparable from the issue of sustainability. This study is designed using quantitative approach. The data collected by self-administered questionnaire to 300 palm stakeholders. The results indicated that the social variable has strong contribution to sustain the palm oil as one of primary energy source. Also, the economic, environmental and security variables have moderate strength in sustainable palm oil. In addition, the sustainable palm oil model which is built from 20 indicators depicts that the concern of plantation companies in fostering smallholders and communities around the plantation is the strongest indicator, while the indicator of protecting endangered plant and animal species and predatory animals in the natural cycle is the weakest indicator of variables in influencing sustainable palm oil in Nagan Raya Regency. Keywords : Palm oil, sustainable model, central to Aceh’s palm oil production JEL Classifications: Q12, Q15, Q16, Q43 DOI: https://doi.org/10.32479/ijeep.10697